0998 PARENTING INTERACTIVE BEDTIME BEHAVIORS AND SLEEP AMONG TODDLERS LIVING IN SOCIOECONOMICALLY DISADVANTAGED HOMES. (28th April 2017) - Ordway, MR; Jeon, S; Canapari, C; Sadler, L; Redeker, N
Abstract: Introduction: Emerging research suggests that sleep duration disparities seen in older children and adults may originate early in life among children living in socioeconomically disadvantaged homes. Parenting may be an important and modifiable influence on sleep in young children. The purpose of this study is to examine the characteristics of sleep and parenting interactive bedtime behaviors (PIBB) among toddlers living in urban socioeconomically disadvantaged homes. Methods: In this cross-sectional study we recruited parents with healthy toddlers from early head start programs and a community clinic. We obtained objective (9 days/nights of actigraphy) measures of the toddlers' sleep and subjective measures of parenting interactive behaviors. Using the Parental Interactive Bedtime Behavior Survey and subscales (active physical comforting, encourage autonomy, settle by movement, passive physical comforting, social comforting), we examined the associations between PIBB and toddler's sleep characteristics. Results: The sample included 33 toddlers (Mean age=1.33 years, SD=.54). The toddlers' sleep duration averaged 8.22 hours (SD=.86). There were statistically significant moderate associations between sleep duration and parents' passive physical comforting (PPC) (r=-.41, p=.02). Intra-individual variability in the amount of wake after sleep onset (WASO) was also significantly associated with total PIBB and PPC (r=.37, p=.05; r=.52, p=.002, respectively). Intra-individual variability in the amount of sleep fragmentation within toddlers was significantly associated with total PIBB (r=.36, p=.05). Conclusion: While active physical comforting (e.g. rocking to sleep, patting or rubbing child's back) is most commonly associated with sleep patterns in infancy and toddlerhood among samples of higher socioeconomic status, findings from this study suggest a stronger association between PPC (e.g. presence of the parent in the room to fall asleep) and less sleep duration and more individual variability in night wakenings. These results will inform future intervention development that may address the role of parenting behavior in promoting health sleep early in life. Support (If Any): KL2 TR000140 from the National Center for Advancing Translational Science (NCATS) 1K23NR016277-01A1 from the National Institute of Nursing Research